Kinerja Aparatur dalam Memediasi Kreativitas dan Inovasi Terhadap Keberhasilan Penerapan e-Kelurahan - Dio Caisar Darma; Siti Maria; Tri Cicik Wijayanti (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2021)
e-Government adalah pemanfaatan teknologi informasi dan komunikasi dalam proses pemerintahan untuk meningkatkan efisiensi, efektivitas, transparansi, dan akuntabilitas penyelenggaraan pemerintahan. Fokus penelitian bertujuan untuk menganalisis tingkat pengaruh Kreativitas dan Inovasi pada Keberhasilan Implementasi e-Kelurahan Gunung Panjang melalui Kinerja Aparatur. Untuk mengetahui pengaruhnya, maka digunakan metode Path Analysis. Jenis data primer atau langsung berbasis teknik wawancara terhadap 91 responden pada Agustus-November 2019. Temuan empiris membuktikan bahwa: (1) Kreativitas dan Inovasi secara langsung memiliki pengaruh yang signifikan terhadap Kinerja Aparatur Kelurahan Gunung Panjang Samarinda; (2) Kreativitas dan Inovasi secara langsung memiliki pengaruh yang positif signifikan terhadap Keberhasilan Implementasi e-Kelurahan Gunung Panjang Samarinda; (3) Kinerja Aparatur Langsung memiliki pengaruh positif terhadap Keberhasilan Implementasi e-Kelurahan Gunung Panjang Samarinda; dan (4) Kreativitas dan Inovasi secara tidak langsung memiliki pengaruh yang positif terhadap Keberhasilan Implementasi e-Kelurahan Gunung Panjang melalui Aparatur Kinerja.Kata Kunci: kantor publik; pegawai negeri sipil; teknologi dan informasi; analisis jalur.To what extent is the performance of the apparatus in determining the creativity and innovation of the e-Kelurahan's success? A CaseABSTRACT In the digital era, the use of technology and information has grown very rapidly to help humans in their daily work. This is inseparable from the demands of private companies and public agencies, in order to create a professional character for employees in a sustainable manner. We try to highlight the influence of creativity and innovation on the successful implementation of e-Kelurahan with the role of apparatus performance in Sidomolyo Village, Samarinda City. Path analysis techniques are used to answer the objectives and proposed hypotheses. Data interpretation was supported by survey data for 100 informant units in 2019. They are civilians who are domiciled and are taking care of the administrative needs that get services in the Sidmolyo area, so the purposive sampling technique is very appropriate to describe the characteristics of the informants. As a result, this finding concludes that creativity and innovation have a significant effect on personnel performance. from other direct influences, creativity and innovation have a significant impact on the successful implementation of e-Kelurahan. Then, the performance of the apparatus also has a significant effect on the success of implementing e-Kelurahan. Finally, especially for the indirect effect, creativity and innovation have had a significant effect on the success of implementing e-Kelurahan with the role of good apparatus performance. This study indicates that for theoretical and practical purposes, it is necessary to support the success of public services that synergize human resources and digitalization.Keywords: public office; civil servants; technology and information; path analysis.